WORK-LIFE BALANCE POLICIES AND THEIR EFFECT ON EMPLOYEE JOB SATISFACTION IN REMOTE WORK SETTINGS - Hans Cristian; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2025)
The rapid proliferation of remote work has fundamentally altered the work-life interface, making organizational Work-Life Balance (WLB) policies more critical than ever for employee job satisfaction. This critical review synthesizes existing literature to evaluate the efficacy of these policies in remote settings, revealing significant theoretical and methodological shortcomings. The analysis demonstrates that dominant frameworks often promote a flawed